Factors predicting visual improvement post pars plana vitrectomy for proliferative diabetic retinopathy - Tai, Evelyn Li Min; Goh, Yihui; Wan Hitam, Wan-Hazabbah; Mohd Ali, Haslina (Press of International Journal of Ophthalmology (IJO PRESS), 2017)
誗AIM: To identify factors predicting visual improvement post vitrectomy for sequelae of proliferative diabetic retinopathy (PDR). 誗METHODS: This was a retrospective analysis of pars plana vitrectomy indicated for sequelae of PDR from Jan. to Dec. 2014 in Hospital Sultanah Bahiyah, Alor Star, Kedah, Malaysia. Data collected included patient demographics, baseline visual acuity ( VA ) and post - operative logMAR best corrected VA at 1y. Data analysis was performed with IBM SPSS Statistics Version 22郾0. 誗RESULTS: A total of 103 patients were included. The mean age was 51郾2y. On multivariable analysis, each preoperative positive deviation of 1 logMAR from a baseline VA of 0 logMAR was associated with a post - operative improvement of 0郾859 logMAR (P < 0郾001). Likewise, an attached macula pre - operatively was associated with a 0郾374 (P = 0郾003) logMAR improvement post vitrectomy. Absence of iris neovascularisation and absence of post - operative complications were associated with a post vitrectomy improvement in logMAR by 1郾126 (P = 0郾001) and 0郾377 ( P = 0郾005 ) respectively. Absence of long - acting intraocular tamponade was associated with a 0郾302 (P = 0郾010) improvement of logMAR post vitrectomy. 誗CONCLUSION: Factors associated with visual improvement after vitrectomy are poor pre-operative VA, an attached macula, absence of iris neovascularisation, absence of post - operative complications and abstaining from use of long - acting intraocular tamponade. A thorough understanding of the factors predicting visual improvement will facilitate decision - making in vitreoretinal surgery.